A Proof of Concept of XR Application in the Construction of Logistics Warehouses - Jácome, Jarbas; Alvez, Luís E. M.; Brazileiro, Ricardo (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR); 2024: Anais Estendidos do XXVI Simpósio de Realidade Virtual e Aumentada, 2024)
This proof of concept introduced Pernambuco’s industries to the new possibilities offered by XR technologies. Through the HoloLens 2, SVR 2024 attendees will be able to visualize an example of a logistics warehouse rendered in 3D within the real environment using augmented reality. The logistics company that experienced this PoC expressed interest in further exploring XR applications.